Biological Response of Spodoptera frugiperda to Uses of Vegetable Pesticides Ipomoea pes-caprae Leaf Extract - Olis Dama; Mohammad Lihawa; Hayatiningsih Gubali (International journal of technology and education research, 2026)
This study aims to evaluate the effectiveness of leaf extract (Ipomoea pes-caprae) as a plant pesticide in controlling (Spodoptera frugiperda), focusing on the effect of concentration and method of application on mortality, and feeding activity. This study was conducted to fill the limitations of previous studies that highlighted more pharmacological aspects (Ipomoea pes-caprae) and have not studied its potential as an insecticide against agricultural pests. The method used was a laboratory experiment with a factorial Complete Random Design (RAL), consisting of four concentration levels (0, 1000, 3000, and 5000 mg/L) and three application methods (feed dip, larval spray, and combination), with three replicas. The results showed that larval mortality was influenced by the interaction between concentration and application method, where at small and moderate concentrations the oral method was more effective, while at high concentrations the contact method was more dominant. In addition, the extract is able to significantly suppress eating activities. These findings confirm that the effectiveness of plant-based pesticides is contextual and depends on the entry pathways of the active compounds.